If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(-9x + -18) = 540 Reorder the terms: -5(-18 + -9x) = 540 (-18 * -5 + -9x * -5) = 540 (90 + 45x) = 540 Solving 90 + 45x = 540 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-90' to each side of the equation. 90 + -90 + 45x = 540 + -90 Combine like terms: 90 + -90 = 0 0 + 45x = 540 + -90 45x = 540 + -90 Combine like terms: 540 + -90 = 450 45x = 450 Divide each side by '45'. x = 10 Simplifying x = 10
| 17=4c+17 | | (-99e^2t)+(149e^3t)=0 | | 6(4x+5)=-3(7x-9) | | 15mi=ft | | 17.3=X | | 46=6+5p | | -x+3=2(3-2x) | | 63+x=66.06 | | -4-x+2= | | 3x+9+4x+x=0+0 | | 15x+14y=475 | | 2/3X-(1/7)(2/3X)=400 | | 10f-h^3= | | 18-5x=3x-14 | | X=3/45 | | -3(4+y)=-27 | | 13x-16=x+8 | | 11x-12+4x+12=180 | | 14j+10j=16 | | 4x-y=76 | | -3(4-y)=37 | | 8x+12y=344 | | -4-x-2= | | 3(k+4)=57 | | 5(4x-8)=4(5x-7) | | =5x-4(6x+8) | | 37x-3+72=180 | | 15*m=170 | | 4(x-5)=8-2(x+19) | | 22=5p+7 | | l-(4w)=-2 | | -6m-5=19 |